Síntese e avaliação farmacológica de novos compostos híbridos úteis para tratamento das complicaçôes da anemia falciforme - Melo, Thaís Regina Ferreira de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Sickle Cell Anemia is a genetic blood disease in which there is a mutation in the β-hemoglobin gene. This mutation promotes polymerization of hemoglobin molecules that change the structure of the erythrocyte cytoskeleton promoting sickling of the cell. Moreover, there is increased adhesion of blood cells in the vessel contributing to the increasement of the vaso-occlusive process, the main characteristic of the disease. It is further known that the chronic inflammation associated with the disease contributes to a number of complications and among the process responsible for this proinflammatory cytokine is TNF-α, which is an important target for therapeutic intervention. Hydroxyurea (HU) is the only available drug for treatment and its beneficial effects are associated with the same capacity biotransformation of nitric oxide. The NO plays beneficial effects such as vasodilation, inhibition of platelet aggregation and production of fetal hemoglobin (Hb F), latter has the function of decreasing polymerization of hemoglobin. In this context, continuing the research line that aims at planning , synthesis and pharmacological evaluation of new prototypes drug candidates for the treatment of sickle cell anemia complications, in this work have synthesized a series of four new hybrid compounds ( I- IV) containing the phtalimide (TNF-alfa inhibitory subunit) and furoxan subunits ( nitric oxide donors) according to structural design. The compounds were presented as NO donors. Compounds I-IV were shown to be inhibitors of TNF-α in the immunoassay of this cytokine assay and the compound IV is the most promising inhibiting between 65% in smaller concentrations than the other. In the assay of ADP-induced platelet aggregation, compounds III and IV were able to inhibit platelet aggregation sigficantily. In addition, the compound I after 72 hours was able to increase the gene expression of gamma globin approximately two times the control, at a ...

A Anemia Falciforme (A.F.) é uma doença hematológica genética na qual ocorre mutação no gene da β-hemoglobina. Essa mutação promove polimerização das moléculas de hemoglobina, promovendo alterações (afoiçamento) da estrutura física dos eritrócitos e aumento da adesão das células sanguíneas no vaso contribuindo para o aumento do processo vaso-oclusivo, principal característica da doença. A doença promove um processo inflamatório crônico e há aumento de diversas citocinas pró-inflamatórias, a exemplo do TNF-α, sendo este, portanto um importante alvo para intervenção terapêutica. A hidroxiuréia (HU) é o único fármaco disponível para o tratamento e seus efeitos benéficos estão associados à capacidade de biotransformação da mesma em óxido nítrico. Entretando, a mielotoxicidade e demais efeitos deletérios da HU, torna importante a introdução de novos fármacos que agregue os efeitos benéficos da mesma sem sua potencial toxicidade. O NO desempenha efeitos benéficos tais como: vasodilatação, inibição da agregação plaquetária e produção de hemoglobina fetal (HbF), esta última tem função de diminuir a polimerização da hemoglobina. Nesse contexto, em continuidade com uma linha de pesquisa que visa o planejamento, síntese e avaliação farmacológica de novos protótipos candidatos a fármacos para tratamento das complicações da anemia falciforme, foi sintetizada uma nova série de quatro compostos híbridos inéditos (I-IV) contendo a subunidade ftalimídica (inibidora de TNF-α) e o núcleo furoxânico (doador de NO) espaçados pela subunidade N-acilidrazona. Todos os compostos apresentaram-se como doadores de NO. Os compostos I a IV mostraram-se inibidores de TNF-, sendo o composto IV o mais promissor, inibindo em torno de 65% em concentrações menores que os demais. No ensaio de agregação plaquetária induzida por ADP, os compostos III e IV foram capazes de inibir sigficativamente a ...
Keywords: Anemia falciforme; Hematologia; Oxido nitrico; Hemoglobina; Fármacos; Hematology